A Complicated Case of Congenital Nasal Pyriform Aperture Stenosis: Use of a Long-term Unilateral Nasal Stent. (October 2019) - Li, Carol; Awad, Mahmoud; Maresh, Alison M.
This case describes a full-term baby with pyriform aperture stenosis who failed intranasal dexamethasone and reflux therapy. She underwent repair via a sublabial approach and inferior turbinate reduction. Symptoms initially improved but she was unable to be weaned from intranasal steroids. Three subsequent surgeries ensued, including lysis of synechiae, further turbinate reduction, and placement of custom nasal stents, which failed as they became clogged frequently and were easily dislodged, leading to increased intranasal manipulation and postprocedural inflammation. She was eventually fitted and discharged with a large, unilateral stent. After 8 weeks, the stent was removed; she was tolerating full oral feeds. This case highlights the limitations of surgical repair and describes nontraditional uses of stenting.